Attachment style and filial obligation in the burden of caregivers of dementia patients. (March 2018) - Lee, Juwon; Sohn, Bo Kyung; Lee, Hyunjoo; Seong, Su jeong; Park, Soowon; Lee, Jun-Young
Highlights: Caregiver attachment anxiety positively predicted burden. When obligation was high, attachment avoidance negatively predicted burden. Obligation positively predicted burden among those low in attachment avoidance. Abstract: Insecure attachment styles have been known to predict greater burden in caregivers of dementia patients. However, it has not been tested how filial obligation, which refers to one's sense of duty on helping elderly parents and is especially pronounced in Asian cultures, is involved in that relationship. We sought to identify whether the association between attachment style and caregiver burden differs according to the degree of filial obligation in caregivers of dementia patients. To assess filial obligation in Korean participants, a Korean filial obligation measure was developed. Ninety-eight Korean female caregivers of dementia patients reported their attachment style, filial obligation, burden, and patient behavioral symptoms. Patients' cognitive abilities, daily activity levels, and global dementia severities were obtained from hospital records. When adjusting for caregiver and patient characteristics, greater attachment anxiety predicted higher burden, corroborating literature findings. However, the association of attachment avoidance with burden was contingent on filial obligation: When obligation was high, greater avoidance associated with lower burden, which contrasts with previous negative implications of attachment insecurity. This implies a buffering role of attachment avoidance among those highly obligated. In addition, obligation positively predicted burden among those low in avoidance. This study is the first one to investigate and find conditional associations between attachment style, filial obligation, and caregiver burden. Given that filial obligation tends to be higher in caregivers of Eastern countries, this study provides quantitative evidence that the caregiving process may be different for them.